Belonging to a Community of Research Practice - Clavijo-Olarte, Amparo (Colombian Applied Linguistics Journal, 2015)
Belonging to a community of research practice as applied linguists or as academics in any field is part of our professional life. Being an academic implies, inter alia, creativity in advancing knowledge in the disciplines, which reflects in writing journal articles, presenting papers in conferences, doing research, teaching, tutoring students and publishing. Globally, every higher education institution requires that academics publish in prominent journals to make their work and their institution visible and influence their professional field. However, the questions that arise concerning academic production are how do communities of research support academic production?, How do higher education institutions help novice researchers develop academic writing competences?, What is the place of writing within research? How do institutions foster quality publication?